Improving RF generation conditions in a ferrite-filled transmission line - Karelin, S.Y.; Krasovitsky, V.B.; Magda, I.I.; Mukhin, V.S. (Вопросы атомной науки и техники, 2018)
The paper considers transformation of the short unipolar pulse of electric current in a coaxial transmission line filled with a ferromagnetic into a shock wave, with later generation of quasi-monochromatic radio frequency oscillations. The frequencies and amplitudes of the oscillations are determined by dispersive and non-linear properties of the transmission line, governed by the geometry and size of the line proper, and layered structure and intrinsic dispersion of the ferromagnetic material. The numerical experiments done for a variety of geometrical and material parameters of the line have allowed suggesting technical solutions as to increase in the efficiency of the dcto-rf power conversion.